2018
DOI: 10.3390/catal8080328
|View full text |Cite
|
Sign up to set email alerts
|

NiFeOx as a Bifunctional Electrocatalyst for Oxygen Reduction (OR) and Evolution (OE) Reaction in Alkaline Media

Abstract: This article reports the two-step synthesis of NiFeOx nanomaterials and their characterization and bifunctional electrocatalytic activity measurements in alkaline electrolyte for metal-air batteries. The samples were mostly in layered double hydroxide at the initial temperature, but upon heat treatment, they were converted to NiFe2O4 phases. The electrochemical behaviour of the different samples was studied by linear sweep voltammetry and cyclic voltammetry on the glassy carbon electrode. The OER catalyst acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
1
16
0
2
Order By: Relevance
“…In our previous studies, the bimetallic catalyst Fe 0.3 Ni 0.7 O X /MWCNTS‐Ox was identified as a promising OER catalyst, achieving a current density of 10 mA cm −2 at a potential of as low as 1.55 V versus RHE . This value is comparable to the benchmark OER‐performance of iron‐containing nickel oxide‐based OER catalysts reported in the literature, including NiFeO X , NiFeB X , and NiFe layered double hydroxide (LDH) . In the present work, we used Fe 0.3 Ni 0.7 O X as an OER‐benchmark and incorporated MnO X with a twofold aim: first, to activate the composite for the ORR, and second, to explore potential synergistic interactions among the three transition metals which could lead to enhanced ORR and OER performances.…”
Section: Resultssupporting
confidence: 60%
“…In our previous studies, the bimetallic catalyst Fe 0.3 Ni 0.7 O X /MWCNTS‐Ox was identified as a promising OER catalyst, achieving a current density of 10 mA cm −2 at a potential of as low as 1.55 V versus RHE . This value is comparable to the benchmark OER‐performance of iron‐containing nickel oxide‐based OER catalysts reported in the literature, including NiFeO X , NiFeB X , and NiFe layered double hydroxide (LDH) . In the present work, we used Fe 0.3 Ni 0.7 O X as an OER‐benchmark and incorporated MnO X with a twofold aim: first, to activate the composite for the ORR, and second, to explore potential synergistic interactions among the three transition metals which could lead to enhanced ORR and OER performances.…”
Section: Resultssupporting
confidence: 60%
“…%). All these phases have been shown to be active towards the oxygen evolution in alkaline solutions [39,[43][44][45][46][47][48][49][50]. Their combination may produce a synergistic effect towards the oxygen evolution reaction.…”
Section: Electrochemical Characterization In An Alkaline Electrolysismentioning
confidence: 99%
“…On the other hand, it has been largely demonstrated that a spinel phase is more performing compared the pure Ni oxide and Fe oxide [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…However, the semi-reaction in the process of water splitting, oxygen eVolution reaction (OER), is related to the continuous process of four proton-coupled electron transfer, which requires a higher overpotential at the anode and it therefore undergoes a sluggish reaction dynamics process [11][12][13]. As a consequence, it is particularly valuable for researchers to develop efficient and stable oxygen-evolving catalysts at present [14,15]. Particularly, some noble metal catalysts, including IrO 2 and RuO 2 , are deemed to the most efficient and robust electrocatalysts for water oxidation [16,17].…”
Section: Introductionmentioning
confidence: 99%